Phytochemical and Antioxidant Capacity Test on Turmeric Extract (Curcuma Longa) Traditionally Processed in Bali - Permatananda, Pande Ayu Naya Kasih; Aryastuti, Anak Agung Sri Agung; Cahyawati, Putu Nita; Udiyani, Desak Putu Citra; Wijaya, D.; Pandit, I Gde Suranaya; Wirajaya, Anak Agung Ngurah Mayun (Badan Riset dan Inovasi Daerah Provinsi Bali, 2020)
Purpose: The purpose of this study was to determine the ways and objectives of the use of turmeric by Balinese, as well as the phytochemical content and antioxidant capacity of turmeric extract which is traditionally processed in Bali. Research methods: The method and purpose of utilizing turmeric were obtained through observation and interviews with 900 Balinese respondents. Quantitative phytochemical tests include starch, protein, flavonoid, tannin, phenol and vitamin C levels and qualitatively for the presence of triterpenes, steroids, alkaloids, and saponins. Antioxidant capacity was measured using the DPPH method. Findings: Through this research, we found there were only 36.8% of respondents had ever used turmeric as a traditional medicine. Utilization of turmeric was mostly in the form of loloh or traditional drinks. Phytochemical test results showed turmeric extract had 67.38% starch, 3.42% protein, 2709.39 mg/100 gr flavonoids, tannins 291.64 mg/100gr, phenol 1584.04 mg/100 gr, and vitamin C 0.06 mg/100gr. Qualitatively, turmeric extract contained triterpenes, alkaloids, and saponins, but did not contain steroids. The antioxidant capacity of turmeric extract was 70.9 mg/L GAEAC. Implications: Turmeric extract is a traditional medicine made from nature that is most commonly used by Balinese and very potential to be developed as an antibacterial, antioxidant, anti-inflammatory, or other benefits that still need further investigation.